SENSORY ACCEPTABILITY, ANTIOXIDANT ACTIVITIES, AND TOTAL PHENOLICS OF KOMBUCHA FROM TAYU GREEN TEA (Camellia sinensis L.) - Sutyawan Sutyawan; Novidiyanto Novidiyanto (Jurnal Gizi dan Pangan Soedirman, 2026)
Kombucha is a fermented tea beverage with health benefits due to its antioxidant, antidiabetic, and antibacterial properties. Kombucha can be made from various types of tea. Green tea from Tayu leaves is a specialty of Ketap Village, West Bangka Regency. Previous research has shown that kombucha from Tayu black tea has a higher antioxidant content than commercial tea. This study compared the sensory acceptability, antioxidant activity, and total phenols of kombucha made from Tayu green tea to commercial tea. The research design used was purely experimental in food production. The sensory characteristics were determined through organoleptic testing involving 30 semi-trained panelists. Total phenolics were tested using the Folin-Ciocalteu method, and antioxidant activity using the FRAP (Ferric Reducing Antioxidant Power) method. Statistical analysis was conducted using an independent sample t-test and Mann Whitney u test. The results showed that the acceptability of kombucha from Tayu green tea was significantly higher (p<0.05) in all aspects (color, smell, and taste) than commercial tea. The antioxidant activity of kombucha from Tayu green tea was higher than that of commercial tea, but not significantly different (p>0.05). The total phenol content was the same for both types of kombucha. The acceptability and antioxidant activity of green kombucha made from Tayu green tea are higher than those made from commercial tea. Research recommends examining the effect of fermentation duration and sugar concentration on the antioxidant activity, polyphenols, and acceptability of Tayu tea leaf kombucha.